Local Area Network - Asdi Aulia (Center for Economic Studies Universitas Katolik Parahyangan, 2001)
Local area network is an important aspect in any organizations that employ computer-based information systems. In order to exchange and share data effectively and efficiently the computer systems must be connected in a network, called local area network. This paper discusses the basic knowledge about local area network, including the components, advantages and disadvantages, and security issues.